Clinical Use of a New High-Sensitivity Cardiac Troponin I Assay in Patients with Suspected Myocardial Infarction. (1st November 2019) - Boeddinghaus, Jasper; Twerenbold, Raphael; Nestelberger, Thomas; Koechlin, Luca; Wussler, Desiree; Meier, Mario; Troester, Valentina; Zimmermann, Tobias; Badertscher, Patrick; Wildi, Karin; Rubini Giménez, Maria; Lopez-Ayala, Pedro; et al.
Abstract: BACKGROUND: We aimed to validate the clinical performance of the high-sensitivity cardiac troponin I [VITROS ® Immunodiagnostic Products hs Troponin I (hs-cTnI-VITROS)] assay. METHODS: We enrolled patients presenting to the emergency department with symptoms suggestive of acute myocardial infarction (AMI). Final diagnoses were centrally adjudicated by 2 independent cardiologists considering all clinical information, including cardiac imaging: first, using serial hs-cTnT-Elecsys (primary analysis) and, second, using hs-cTnI-Architect (secondary analysis) measurements in addition to the clinically used (hs)-cTn. hs-cTnI-VITROS was measured at presentation and at 1 h in a blinded fashion. The primary objective was direct comparison of diagnostic accuracy as quantified by the area under the ROC curve (AUC) of hs-cTnI-VITROS vs hs-cTnT-Elecsys and hs-cTnI-Architect, and in a subgroup also hs-cTnI-Centaur and hs-cTnI-Access. Secondary objectives included the derivation and validation of an hs-cTnI-VITROS-0/1-h algorithm. RESULTS: AMI was the adjudicated final diagnosis in 158 of 1231 (13%) patients. At presentation, the AUC for hs-cTnI-VITROS was 0.95 (95% CI, 0.93–0.96); for hs-cTnT-Elecsys, 0.94 (95% CI, 0.92–0.95); and for hs-cTnI-Architect, 0.92 (95% CI, 0.90–0.94). AUCs for hs-cTnI-Centaur and hs-cTnI-Access were 0.95 (95% CI, 0.94–0.97). Applying the derived hs-cTnI-VITROS-0/1-h algorithm (derivation cohort n = 519) to the validation cohort (n = 520), 53% of patients were ruled out [sensitivity, 100% (95% CI, 94.1–100)] and 14% of patients were ruled in [specificity, 95.6% (95% CI, 93.4–97.2)]. Patients ruled out by the 0/1-h algorithm had a survival rate of 99.8% at 30 days. Findings were confirmed in the secondary analyses using the adjudication including serial measurements of hs-cTnI-Architect. CONCLUSIONS: The hs-cTnI-VITROS assay has at least comparable diagnostic accuracy with the currently best validated hs-cTnT and hs-cTnI assays. ClinicalTrials.gov Identifier: NCT00470587.